Genotype and Phenotype Analysis in X-Linked Hypophosphatemia - Park, Peong Gang; Lim, Seon Hee; Lee, HyunKyung; Ahn, Yo Han; Cheong, Hae Il; Kang, Hee Gyung (Frontiers in Pediatrics, 2021)
Background X-linked hypophosphatemia (XLH) is the most frequent form of hypophosphatemic rickets and is caused by mutations in the PHEX gene. We analyzed genotype-phenotype correlations in XLH patients with proven PHEX mutations. Methods PHEX mutations were detected in 55 out of 81 patients who clinically presented with hypophosphatemic rickets. The patients were grouped into nontruncating (n = 9) and truncating (n = 46) mutation groups; their initial presentation as well as long-term clinical findings were evaluated according to these groups. Results Initial findings, including presenting symptoms, onset age, height standard deviation scores (SDS), and laboratory tests, including serum phosphate level and tubular resorption of phosphate, were not significantly different between the two groups (onset age: nontruncating mutation group, 2.0 years, truncating mutation group, 2.2 years; height SDS: nontruncating mutation group, -1.9, truncating mutation group, -1.7; serum phosphate: nontruncating mutation group, 2.5 mg/dL, truncating mutation group, 2.6 mg/dL). However, at their last follow-up, the serum phosphate level was significantly lower in patients with truncating mutations (nontruncating mutation group: 3.2 mg/dl, truncating mutation group: 2.3 mg/dl; P value 0.006). Additionally, 62.5% of patients with truncating mutations developed nephrocalcinosis at their last follow-up, while none of the patients with nontruncating mutations developed nephrocalcinosis (P value 0.015). Orthopedic surgery due to bony deformations was performed significantly more often in patients with truncating mutations (52.3% vs 10.0%, P value 0.019). Conclusion Although considerable inconsistency exists regarding the correlation of truncating mutations and their disease phenotype in several other studies, we cautiously suggest that there would be genotype-phenotype correlation in some aspects of disease manifestation after long-term follow-up. This information can be used when consulting patients with confirmed XLH regarding their disease prognosis.